Analisa Kadar Kalsium (Ca) Pada Daun Kelor (Moringa oleifera) - Mardiah Mardiah (Jurnal Ilmu Alam dan Lingkungan, 2017)
Moringa leaves (Moringa oleifera) is one part of the Moringa plant which can be consumed as a vegetable and mineral content in the form of calcium which is quite a lot. Calcium is a mineral needed by the human body, it has an important role in various stages of metabolism. Calcium is useful to prevent osteoporosis, blood clotting and building bones stronger teeth. Lack of calcium in the body can lead to calcium deficiency, which affects the various complaints in the bones, teeth, blood, nerves, and metabolism. The purpose of this study to analyze the levels of calcium (Ca) in the leaves of Moringa (Moringa oleifera). Type of research is an observational laboratory with Quantitative Analysis technique. The sample used in this study were 5 samples. Sampling technique is an accidental sampling. Furthermore, each sample in dry digestion is then examined at an atomic absorption spectrophotometer, at a wavelength of 422.7 nm. Based on the research results obtained by the levels of calcium in the leaves of Moringa is 7059.2 mg/L, 4652.5 mg/L, 3.180 mg/L, 2078.9 mg/L, and 9268.7 mg/L indicates that in the leaves of Moringa contains a lot of calcium. From this study,  it can be concluded in the presence of calcium that can meet the needs of the mineral in the human body